Development of a wind turbine driven by longitudinal vortex: Wind tunnel experiment to investigate the basic characteristics of the wind turbine using a single circular cylinder blade. Issue 210 (March 2021) - Sakamoto, Kasumi; Hemsuwan, Withun; Takahashi, Tsutomu
Abstract: In this study, the basic rotation and output torque characteristics of a longitudinal vortex wind turbine (LV-WT) were investigated by using a wind tunnel experiment. This wind turbine uses a circular cylinder with a diameter d as the driving blade, and a ring-shaped plate with width w ​= ​d is installed behind the cylinder blade with a gap s . A steady lift force to sustain the rotational motion is generated by the longitudinal vortex formed near the intersection of the cylinder blade and the ring plate. The gap ratio s/d is the most dominant parameter for the performance of the LV-WT, and the output torque and efficiency are maximum at s/d  ​= ​0.35. A wider ring plate and flanges attached to the blade are promising techniques to improve the performance of the LV-WT. The lift coefficient C l is approximated by a decreasing linear function of the velocity ratio λ = (rotational velocity V )/(free flow velocity U ), as predicted in the preceding numerical study of the authors. Using the drag coefficient determined by the loaded experiment, the performance characteristics of LV-WT are predicted for the widely varying conditions.